Traction Energy Consumption of Electric Locomotives and Electric Multiple Units at Speed Restrictions - Fischer, Sz. (Acta Technica Jaurinensis, 2015)
In this article the author reports the measurements made by traction measuring car of Railway Engineering and Metrological Service Centre (REMSC) in the research and development work “Complex investigation of reduction possibilities of additional costs due to speed restrictions on electric traction railway lines”. As results it can be stated that a correction parameters in the research and development work made between 2008 and 2010 should be changed because of specifying. These parameters can be used for calculation of additional acceleration energy after speed restriction sites.